(untitled) (Fiep Bulletin - online, 2011)
To observe previous Cuba the 1950 and the Cuba of today sends to the observer to a contemplation state and surprise, therefore at the same time where many pointers had gone up much others had not obtained to support themselves the same in level. It enters the profits of the Revolution is the Physical Education, mainly with its manifestation "Sport". What before it was of practical exclusive to chaste a select one, currently is one of the flags that the idea supports that the Revolution "gave certain". The objective of the present work is to observe the occurred transformations in the Cuban society for the prism of the sport with intention to understand others sides of the movement that took the power has 50 years more than behind. For such we carry through a research of bibliographical and documentary character for the literal construction, having in the qualitative analysis the inquiry components. We understand that the nickname anachronistic that Cuba receives from the developed countries if from the one for the influence that the technology imposed in all the components of the social life and human being, and intensifying the search for the power and its attributions in such a way. The universality that Cuba attributes to the sport has been evidences in any reflection of that the sport can contribute for the development of a nation. Being thus, the combat the sportive action mercantilist, the condition of inserted imposition in this segment and the condition of alienation imposed for the process of capitalist globalization are negative elements that the universality in Cuba aimed at and aim at to dismiss.